Comparative study on photocatalytic efficiency of Mg doped CuFeO2 versus TiO2 doped CuFeO2 delafossite based on their application for the removal of tartrazine yellow dye - Sayam Bhattacharyya; Sk Aakash Hossain; Sampad Sarkar; Papita Das (Chemistry of Inorganic Materials)
The present work highlights the comparative analysis between Mg doped CuFeO2 (named as Mg-CFO) and TiO2/CuFeO2 composite (named as TiO2-CFO) for the photodegradation of TZ dye in aqueous solution. Physicochemical tests like XRD, FTIR, FESEM, EDX was done for both the composites. The pHpzc values of Mg-CFO and TiO2-CFO were determined to be 9.34 and 9.0 respectively for which both photocatalysts gave good removal efficiency of anionic TZ in an acidic or lower pH region. Mg-CFO degraded 87 ​% of 20 ​mg ​L−1 of TZ in 100 ​mL of solution at 50 ​mg dosage, under pH∼2, at 130 ​rpm and 30 ​°C temperature showing a rate constant of 0.00602 min−1 and TiO2-CFO degraded 91 ​% of TZ dye under the same conditions showing a rate constant of 0.00637 min−1. The quenching test showed that both photocatalysts had generated O2°- radicals as the primary species and OH° as the secondary species. In general, TiO2-CFO composite was proved to be a comparatively better photocatalyst than Mg-CFO sample.